Public Dental Service personnel facing a major health care reform in Finland - Widström, Eeva; Tiira, Hannele; Tillberg, Anders (BDJ Open, 2019)
Objectives - A health care reform will replace the health care and social services centred on public provision with a market-oriented system and enhanced competition between public and private sectors. The aim was to ascertain Public Dental Services (PDS) changes personnel anticipated and how dental services in the new “public” undertakings could be made more cost-efficient. Materials and methods - An electronic questionnaire was sent to the Chief Dentists of a random sample of 12 PDS units in southern and northern Finland for distribution to their personnel; 71.0% responded. Results - Most respondents (64.3%) believed that their PDS unit would not change. However, 45.4% foresaw a merger with another unit. More dentists (51.2%) were aware of market- and competition-oriented organisational forms to be introduced in the public sector than dental hygienists (35.0%) and dental assistants (27.3%; p < 0.01). Only 12.4% thought of moving to the private sector. To increase cost-efficiency in the new system, a majority suggested improvement in preventive care (79.8%) and increased use of dental hygienists (75.7%). A smaller proportion suggested longer opening hours (23.1%), higher patient fees (17.9%) or more paying patients (12.4%). Discussion -Public sector employees had little knowledge and understanding of the coming reform and were badly prepared for competition with the private sector.